Solusi Berbasis Ekonomi Syariah terhadap Maraknya Pinjaman Online di Kalangan Gen Z - Dewi, Fertika Puspita; Widiana, Nada (Jurnal EMT KITA, 2026)
The development of digital technology has driven the growth of online lending services (commonly known as pinjol) in Indonesia, particularly among Generation Z. This phenomenon has led to various issues, ranging from consumptive behavior to the entanglement of young people in riba (usury) practices prohibited in Islam. This study aims to analyze the factors that drive consumptive behavior among Gen Z in using online loans and to offer Sharia-based economic solutions to address these problems. The research employs a qualitative method, with data collection techniques that included in-depth interviews with five informants, comprising experts and practitioners in Islamic economics and Islamic fintech, along with documentation studies, and a review of relevant literature. In addition, supplementary data were obtained from a limited questionnaire administered to 19 Generation Z respondents to reinforce the interview findings. The findings indicate that ease of access, a consumptive lifestyle, and a lack of Islamic financial literacy are the main factors behind the widespread use of online loans among Gen Z. The proposed solutions include Islamic financial literacy education, strengthening of regulations, and the development of Sharia-compliant financial technology (fintech). This study is expected to serve as a reference for policymakers in formulating strategies for the prevention and management of online lending issues in accordance with Islamic principles in Indonesia.